Bioanalytical Method Development and Validation and its Applications in Pharmacy – An Overview (Asian Journal of Pharmaceutics (AJP), 2024)
Bioanalytical methods play a critical role in the pharmaceutical industry, providing essential tools for drugdevelopment, pharmacokinetics, and therapeutic drug monitoring. This review discusses the principles ofbioanalytical method development and validation, highlighting key techniques such as chromatography, massspectrometry, and immunoassays. It further explores the applications of these methods in various areas ofpharmacy, including drug formulation, clinical trials, and personalized medicine. Challenges and future directionsin bioanalytical method development are also addressed.